Candida spp. em mucosa oral de pacientes convivendo com HIV/AIDS - Seerig, Mariana Manzoni (2022)
Introduction: Candida spp. is the is the predominant species associated with oral fungal infections in HIV-positive patients. Candida spp. species colonizes mucosal surfaces under normal healthy conditions. However, under immunocompromising conditions, such as HIV-positive patients, the colonization may turn into a symptomatic infection. The symptomatic infection clinical forms include pseudomembranous candidiasis, erythematous candidiasis and angular cheilitis. While fluconazole the most commonly drug used to treat oral fungal infections, it has increased the number of Candida spp. species resistant to this drug. Thus, there is a claim to establish the Candida spp. species sensitivity profile for fluconazole, in order to provide the most effective treatment for HIV-positive patients. Objective: to estimate the prevalence of Candida spp. in the oral mucosa of HIV-positive patients, to describe epidemiological features in this population, to evaluate manifestation of oral lesions, factors related to colonization, and the sensitivity profile to antifungal agents. Methods: A cross-sectional study carried out in a Specialized Attention Service (SAE) for people living with HIV in the municipality of Francisco Beltrão, Southeast of Brazil. Samples were obtained by oral swabs. The phenotypic identification of the isolated yeasts occurred after sample collection and was carried out in microbiology laboratories. This identification aimed at the presumptive determination of the species by conventional methods and was based on observing the morphology of colonies. Candida albicans antifungal susceptibility tests were performed for fluconazole, itraconazole, and amphotericin B with the disk diffusion technique using Mueller-Hinton agar (Difco®) according to document M44- A2. Results: Oral swab samples were collected from 234 patients. Candida spp. prevalence in the oral mucosa of patients was 39.46%. The mean age of the patients 44,3 years. Candida albicans was the most prevalent species (91.4%). Oral manifestation were observed in 43.3% of patients and erythematous candidiasis was the most frequent. Regarding the sensitivity profile to antifungal agents, we found a sensitivity of 91.2% to fluconazole, 39.7% to itraconazole, and 100% to amphotericin B.